Prevalence of Intestinal Parasitic Infection among HIV Positive Persons Who Are Naive and on Antiretroviral Treatment in Hiwot Fana Specialized University Hospital, Eastern Ethiopia. (11th June 2013) - Teklemariam, Zelalem; Abate, Degu; Mitiku, Habtamu; Dessie, Yadeta
Abstract : Background . Intestinal parasitic infection affects the health and quality of life of people living with HIV. This study was aimed to determine the prevalence of intestinal parasites among HIV positive individuals who are naive and who are on antiretroviral treatment (ART) in Hiwot Fana Specialized University Hospital, Eastern Ethiopia. Methods . A comparative cross-sectional study was conducted on 371 (112 ART-naive group and 259 on ART) HIV positive individuals. Stool specimens were collected and examined by direct wet mount, formol ether concentration technique, and modified ziehl-Neelsen methods. Results . The overall prevalence of intestinal parasitic infections was 33.7%; it was significantly higher among the study participants who were ART-naive group (45.5%) (AOR: 2.60(1.56, 4.34)) and diarrheic (53.3%) (AOR: 2.30(1.34, 3.96)) and with CD4 count <200 cells/ μ L (46%) (AOR: 2.07(1.06, 4.04)). The most commonly identified parasites were Entamoeba histolytica/E. dispar (13.5%), Giardia lamblia (8.1%), Strongyloides stercoralis (4.0%), and Cryptosporidium species (2.2%). Conclusion . HIV positive individuals with diarrhea and low CD4 count and ART naive groups were more infected with intestinal parasites than their counterparts. Early stool examination and treatment of intestinal parasites for HIV/AIDS patients is essential.